The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4236/jssm.2010.32025
|View full text |Cite
|
Sign up to set email alerts
|

Employee’s Personality Traits, Work Motivation and Innovative Behavior in Marine Tourism Industry

Abstract: The purpose of this study is to understand the relationship among marine tourism employee's personality traits, work motivation and innovative behavior. In order to meet this purpose, the study conducts questionnaire survey. Questionnaire sample of 250 has been handed out and 215 valid samples have been collected. The results show that employees with higher intrinsic work motivation are more likely to generate innovative behavior. The compensation in extrinsic work motivation has a positive effect on employee'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 11 publications
0
30
0
3
Order By: Relevance
“…This study also provides external validity to psychological capital by conducting research in an eastern context, as the construct is developed and primarily tested in a Western context. Individual’s traits, styles and skills may effect innovative work behavior like problem-solving style (Scott & Bruce, 1998), self-leadership competencies (Carmeli, Meitar, & Weisberg, 2006), self-esteem and perceived insider status in the organization (Chen & Aryee, 2007), personality (Sung & Choi, 2009), proactivity (Kim, Hon, & Lee, 2010), expected positive performance outcomes (Yuan & Woodman, 2010), and commitment (Jafri, 2010). This study advances the literature by adding psychological capital as another crucial individual-level factor for innovative work behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This study also provides external validity to psychological capital by conducting research in an eastern context, as the construct is developed and primarily tested in a Western context. Individual’s traits, styles and skills may effect innovative work behavior like problem-solving style (Scott & Bruce, 1998), self-leadership competencies (Carmeli, Meitar, & Weisberg, 2006), self-esteem and perceived insider status in the organization (Chen & Aryee, 2007), personality (Sung & Choi, 2009), proactivity (Kim, Hon, & Lee, 2010), expected positive performance outcomes (Yuan & Woodman, 2010), and commitment (Jafri, 2010). This study advances the literature by adding psychological capital as another crucial individual-level factor for innovative work behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Amo and Kolvereid (2005) pointed out that employees' intrapreneural personality has a significant impact on innovative behaviour. Chen, Wu and Chen (2010) found that three personality traits -agreeableness, extraversion and openness to experience -positively correlated with idea generation and idea promotion stages of innovative employee behaviour.…”
Section: Enabling Academics' Innovative Capabilities For Sustainable mentioning
confidence: 99%
“…It is very tough to meet these transformational challenges (Chen et al, 2010), and even harder to sustain the position and maintain the standard in this competitive environment (Singh & Singh, 2010). Services organizations are the substantial globally, and health organization have top priority from all services organizations worldwide because they deal with the health of humans.…”
mentioning
confidence: 99%